A Comparison Study of Age and Colorectal Cancer-Related Gut Bacteria - Zhang, Yu-Kun; Zhang, Qian; Wang, Yu-Liuming; Zhang, Wei-Yuan; Hu, Han-Qing; Wu, Hong-Yu; Sheng, Xiang-Zong; Luo, Kang-Jia; Zhang, Hao; Wang, Meng; Huang, Rui; Wang, Gui-Yu (Frontiers in Cellular and Infection Microbiology, 2021)
Recently, intestinal microbiota has gained much interests and a series of researches proved that gut bacteria played a significant role in various malignancies, especially in colorectal cancer (CRC). In this study, a cohort including 34 CRC patients (average age=65 years old), 26 young volunteers (below 30 years old) and 26 old volunteers (over 60 years old) was enrolled. 16S ribosomal RNA gene sequencing was used to explore the fecal bacteria diversity. The operational taxonomic unit (OTU) clustering analysis and NMDS (non-metric multidimensional scaling) analysis were used to separate different groups. Cluster of ortholog genes (COG) functional annotation and Kyoto encyclopedia of genes and genomes (KEGG) were used to detect enriched pathways among three groups. Community separations were observed among the three groups of this cohort. Clostridia, Actinobacteria, Bifidobacterium, and Fusobacteria were the most enriched bacteria in young group, old group, and CRC group respectively. Also, in young, old and CRC group, the ratio of Firmicutes/Bacteroidetes was increased sequentially despite no statistical differences. Besides, COG showed that transcription, cell wall/membrane/envelope biogenesis, inorganic ion transport and metabolism and signal transduction mechanisms were differentially expressed among three groups. KEGG pathways associated with ABC transporters, amino sugar and nucleotide sugar metabolism, arginine and proline metabolism and aminoacyl-tRNA biosynthesis also showed statistical differences among three groups. These results indicated that the intestinal bacterial community varied as age changed and was related to CRC, and we discussed that specific bacteria enriched in the young and old group may exert a protection function, while bacteria enriched in CRC group may promote the tumorigenesis.